Balancing Reproductive Rights and Fetal Protection: Criminal Accountability of Doctors in Rape-Induced Abortions - Muhammad, Reiza; Lolita, Citra; Fikri, Ahmad Ma’mun (Research Horizon, 2025)
Unwanted pregnancies, particularly those resulting from rape, create complex legal and ethical conflicts in Indonesia, balancing a woman’s reproductive autonomy and psychological health against fetal protection. This study analyzes criminal accountability and sentencing of doctors in rape-related abortion cases under Indonesian law. Using a normative juridical method, it examines secondary legal sources, including the Criminal Code, Law Number 17 of 2023 on Health Law, Government Regulation Number 2 of 2025 on Reproductive Health, and judicial precedents. Findings show that a doctor’s liability depends on strict compliance with legal exceptions, including proof of rape, adherence to the fourteen-week gestational limit, and procedural standards such as competent medical teams and authorized facilities. Judicial evaluation emphasizes the presence or absence of justification or excuse, which can mitigate or aggravate penalties. The implementation of Criminal Code Number 1 of 2023 and Government Regulation Number 2 of 2025 provides clearer legal protection for medical professionals, resolving longstanding ethical and legal dilemmas. The legal framework now balances the rights of rape victims with the accountability of medical practitioners, ensuring proportional sanctions, safeguarding human rights, and enhancing legal certainty in reproductive health cases.